Effect of Exercise Program for Injured Football Players: A Systematic Review and Meta-Analysis - Yun, Cheong-Gu; An, Chang Sik; Kim, Jeong-Lae (International Journal of Intelligent Systems and Applications in Engineering, 2022)
This study aimed to investigate and analyze the effects of exercise programs for injured footballers on pain, muscle strength, range of motion, functional performance ability, and balance through a meta-analysis. To examine the effects of exercise programs on injury recovery and improvement in football players, a systematic literature review and meta-analysis, based on twenty-four papers published in Korea and other countries from the 2000s to the present, were conducted. The results of the meta-analysis are as follows. Overall, exercise was effective for football players with experience in getting injured. According to the results, while muscle strength, range of movement and functional performance would show statistically significant improvement, pain and balance would not. The findings on the individual sub-factors are as follows. First, according to the findings of the meta-analysis, the hypothesis that exercise programs applied to football players would influence pain could not be accepted, which means that exercise is not effective in relieving pain. Second, according to a meta-analysis, the hypothesis that exercise programs applied to football players would influence muscle strength was upheld, which means that exercise is effective in improving muscle strength. Third, according to the meta-analysis, the hypothesis that exercise programs applied to football players would influence the range of motion was upheld, which means that exercise is effective in improving the range of motion. Fourth, according to a meta-analysis, the hypothesis that exercise programs applied to football players would affect functional performance was upheld, which means that exercise programs are effective in improving performance ability. Fifth, according to the meta-analysis, the hypothesis that exercise programs applied to football players would influence balance ability was not significant, which means that exercise is not effective for improving balance.